Recent advances in hydrogels as strategy for drug delivery intended to vaginal infections - dos Santos, Aline Martins [UNESP]; Carvalho, Suzana Gonçalves [UNESP]; Araujo, Victor Hugo Sousa [UNESP]; Carvalho, Gabriela Corrêa [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2020)
Vaginal infections represent a clear women health problem due to the several issues as high recurrence rate, drug resistence and emergence of persistent strains. However, achieving improvements in therapeutic efficacy by using conventional formulations intended to vaginal drug delivery remains as a challenge due to anatomy and physiology of the vagina, since the secretion and renewal of vaginal fluids contribute to the removal of the dosage form. Hydrogels have been widely exploited aiming to achieve drug delivery directly into vaginal mucosa for local therapy due to their attractive features as increased residence time of the drug at the action site and control of drug release rates. Some polymers can aggregate specific properties to hydrogels as mucoadhesive, stimuli-responsive and antimicrobial, improving their interaction with the biological interface and therapeutic response. In this review, we highlight the advances, advantages and challenges of the hydrogels as drug and/or nanocarrier vehicles intended to the treatment of vaginal infections, emphasizing also the polymers and their properties more explored on the design these systems to improve the therapeutic effect on the vaginal tissue. In addition, this review can contribute for better exploitation these systems in search of new local treatments for bacterial vaginosis, candidiasis and trichomoniasis.
Keywords: Drug delivery systems; Hydrogels; Vaginal application; Vaginal infections